HUBUNGAN KECOCOKAN ANTARA TIPE KEPRIBADIAN DAN MODEL LINGKUNGAN BELAJAR DENGAN MOTIVASI BELAJAR PADA MAHASISWA PGSD UNIVERSITAS ACHMAD YANI BANJARMASIN - Alpha Ariani (Universitas Muhammadiyah Surakarta, 2014)
Primary Schools aims to form the younger generation who have morals, values andcharacter that tends to be a productive, creative, innovative, and affective . Elementaryschool teachers are one of the key success in shaping the next generation thereforeelementary school teachers must have the professional ability, attitude and personality.University Achmad Yani Banjarmasin as one of the colleges that will generate prospectiveelementary teachers has to make efforts so that the demands of the professionalneeds of elementary school teachers in the community can be met. Teacher professionalmust have pedagogical, social competence, professional competence, and personalitycompetence. Several efforts should be made starting from the right curriculum, condusivelearning process, quality of faculty, and building positive character of the student. Basedon preliminary observations, primary education students come from many levels. Besides,they have a variety of purposes and reasons for studying. This leads to the diversityof motivation in their studies .Therefore, it is necessary to study on CompatibilityRelationship Between Personality Type and Model Learning Environment With StudentsLearning Motivation. The result of this study can be used as one consideration in selectionof new students to enter primary education department.